Theoretical optimization of electrode design parameters of Si based anodes for lithium-ion batteries. (February 2018) - Heubner, C.; Langklotz, U.; Michaelis, A.
Graphical abstract: Highlights: Investigation of design criteria and theoretical limits of Si based anodes for LIBs. Optimization of gravimetric and volumetric capacity considering volume expansion. Determination of optimum electrode design parameters (thickness, porosity). Volume expansion narrows design freedom, attainable capacity and rate capability. Limits of Si based anodes are clearly inferior compared to the properties of Si. Abstract: Silicon is considered one of the most promising anode materials for next-generation lithium-ion batteries. However, dramatic volume expansion during the lithiation of silicon complicates its practical implementation. Literature reports nanostructured electrodes, which are capable to accommodate the volume expansion, reducing associated swelling, degradation and capacity fading. However, several phenomena associated with the volume expansion, such as the reduction of the electrode's porosity, are inherent to the system and must be carefully considered for targeted engineering of high-energy lithium-ion batteries. Herein, we determine design criteria of silicon based electrodes, taking into account the volume expansion during lithiation. A "deformation threshold" is defined signifying the minimum value of the initial porosity that must be adjusted to avoid plastic deformation and dramatic reduction of the electrode's porosity during charging. In addition, a "C-rate threshold" is defined, guaranteeing diffusion limited currents not falling below a desired discharge rate. The impact of these theoretical limitations on the electrochemical performance of silicon-based electrodes is analyzed from an engineering point of view. The derived relations are used to optimize the electrode design parameters regarding maximum gravimetric and volumetric capacity.